Eye in the sky: determining NO2 emissions source / Muhammad I'mran Radzuan ... [et al.] - Radzuan, Muhammad I'mran; Shahadan, Muhammad Lutfi; Mohammad Amin, Muhammad Ameerul Hakim; Che Idrus, Zal Aidi; Iffli Efendy, Iman Nuryasmin; Zulhilmi, Nur Aqilah; Sairan, Muhammad Razif; Mohammad Salim, Pauziyah (College of Built Environment, 2023)
Globally, Nitrogen Dioxide (NO2) is a greenhouse gas emissions from human activities.